Worstel met God: Argumenteringstrategieë en hul sosio-retoriese funksie in Psalm 13 - Coetzee, J. (Verbum et ecclesia, 1998)
Wrestle with God. Argumentation strategies and their socio-rhetorical function in Psalm 13: The psalm is approached from the assumption that it was prayed loud in public in order to be overheard by friend andfoe alike. The argumentation strategies in the prayer are investigated and their function in the rhetorical situation exposed. The prayer has both a socio-rhetorical and a religiorhetorical function, the lalter which is of primary importance.